Aphanamixis Polystachya: A Potential Non-Edible Source of Biodiesel in Bangladesh - Khan, Maksudur R.; Ferdous, Kaniz; Deb, Anjan; Ferdous, Jannatul; Uddin, M. Rakib; Islam, M. A. (Bangladesh Journals OnLine (BanglaJOL), 2013)

(untitled)
This paper represents an attempt that was made to prepare Biodiesel from a non-edible source, Aphanamixis Polystachya (Pitraj). Oil was extracted from the seed by mechanical press method. Various properties of raw oil such as viscosity, Free Fatty Acid (FFA) content, specific gravity, saponofication value etc. were measured by standard methods. FFA content of raw oil was found higher, so the acid catalysed two step method, acid catalysed esterification followed by base catalysed transesterification, was studied. Various reaction parameters such as oil to methanol ratio, catalyst wt%, reaction time and temperature were optimized for both esterification and transesterification reaction. 1HNMR of prepared biodiesel and raw oil was studied which confirms the conversion of oil to biodiesel. Finally, the various properties of produced Biodiesel, such as viscosity, FFA, specific gravity, iodine value, cetane index, calorific value etc. were measured and compared with biodiesel and petro-diesel standards.